PENERAPAN METODE REWARD DAN PUNISMENT DALAM PEMBINAAN DISIPLIN DAN PRESTASI MAHASANTRI MA’HAD AL-JAMI’AH IAIN CURUP - Tri Wati (UIN Fatmawati Sukarno Bengkulu, 2018)
This research is motivated by the implementation of reward and punisment methods that are applied at the Ma’had Al-Jami’ah IAIN Curup as an effort to improve discipline and achievement, this method is suitable for use because it can have a happy and deterrent effect but most of students still have lower discipline and achievement. This research aims to explain the implementation, factors and benefits of reward and punisment method in improving discipline and achievement mahas- antri. This study uses field research methods with qualitative descriptive analysis, data sources used are primary data sources and secondary data sources, data collection using observation, interview and documentation techniques and using analytical techniques namely data collection, data reduction, data presentation and the conclusions, as for the validity of the data the researcher used source triangulation. The results showed that the implementation of the reward method and punisment were applied in accordance with the existing regulations but the rewards were very limited and only given once a year in a gebyar ma’had activity, while the punisment was given by the ma’had management so that there were still many students breaking, the factor of the implementation of this reward method is mahasantri and the benefits of implementation of this reward method can add to the spirit of learning, learning to be responsible, and familiarize the mahasantri practice discipline appreciate the time and obey the rules